Use of genomics to explore AMR persistence in an outdoor pig farm with low antimicrobial usage. Issue 3 (28th March 2022) - Storey, Nathaniel; Cawthraw, Shaun; Turner, Olivia; Rambaldi, Margherita; Lemma, Fabrizio; Horton, Robert; Randall, Luke; Duggett, Nicholas A.; AbuOun, Manal; Martelli, Francesca; Anjum, Muna F.
Abstract : Food animals may be reservoirs of antimicrobial resistance (AMR) passing through the food chain, but little is known about AMR prevalence in bacteria when selective pressure from antimicrobials is low or absent. We monitored antimicrobial-resistant Escherichia coli over 1 year in a UK outdoor pig farm with low antimicrobial usage (AMU) compared to conventional pig farms in the United Kingdom. Short and selected long-read whole-genome sequencing (WGS) was performed to identify AMR genes, phylogeny and mobile elements in 385 E. coli isolates purified mainly from pig and some seagull faeces. Generally, low levels of antimicrobial-resistant E. coli were present, probably due to low AMU. Those present were likely to be multi-drug resistant (MDR) and belonging to particular Sequence Types (STs) such as ST744, ST88 or ST44, with shared clones (<14 Single Nucleotide Polymorphisms (SNPs) apart) isolated from different time points indicating epidemiological linkage within pigs of different ages, and between pig and the wild bird faeces. Although importance of horizontal transmission of AMR is well established, there was limited evidence of plasmid-mediated dissemination between different STs. Non-conjugable MDR plasmids or large AMR gene-bearing transposons were stably integrated within the chromosome and remained associated with particular STs/clones over the time period sampled. Heavy metal resistance genes were also detected within some genetic elements. This study highlights that although low levels of antimicrobial-resistant E. coli correlates with low AMU, a basal level of MDR E. coli can still persist on farm potentially due to transmission and recycling of particular clones within different pig groups. Environmental factors such as wild birds and heavy metal contaminants may also play important roles in the recycling and dissemination, and hence enabling persistence of MDR E. coli . All such factors need to be considered as any rise in AMU on low usage farms, could in future, result in a significant increase in their AMR burden.